(untitled) (Eurasian Journal of Ecology, 2024)
There are about 60 species of the genus Rheum L. (Polygonaceae) distributed mainly in temperate and subtropical Asia, with the largest number (38 species, including 19 endemics) recorded in China. All species of the genus are used as medicinal plants. According to modern pharmacology, the most important property of the rhubarb root is regulation of the stomach and intestine function, due to its laxative effect; rhubarb also has antipyretic properties and antioxidant activity. The high content of dietary fibers provides protection against cardiovascular diseases, and vitamin K is valuable for the prevention of osteoporosis. However, the active ingredients and their mechanism of action have not been sufficiently studied. Rheum tataricum L., known for its high resistance to drought, salinity, and lack of nutrients is the least studied species of wild rhubarb. The whole plant, and especially the leaves, contains several toxic compounds, in particular anthraquinone glycosides and calcium oxalate crystals. Here we present the results of a comparative analysis of the anatomical and morphological structure of Rh. tataricum plants from ecopopulations growing in the Balkhash and Karatal districts of the Almaty region. We identified the differences due to the weather and climatic conditions of the ecopopulations. It is important to note that many idioblasts containing calcium oxalate were found in the rhizomes of Rh. tataricum, which prevent animals from eating plants and getting poisoned. The number of idioblasts in the central circle of the Rh. tataricum rhizome was smaller in the Balkhash district than in the Karatal district, while the idioblasts were larger in size in the former district. The medicinal and nutritional value of Rh. tataricum growing in a semi-desert environment indicates a high potential of the species in plant breeding, medicine, and as a food source. Key words: Rheum tataricum, extract, pharmacology, antioxidant activity, ecopopulation, morphology.